Planning and managing public relations campaigns : a stategic approach - Gregory, Anne (PR in Practice, 2021)
"Taking a public relations campaign from planning through to implementation can seem overwhelming. Planning and Managing Public Relations Campaigns provides a blueprint for success, and is widely regarded as one of the best 'how-to' guides for students and practitioners. Digestible and easy to read, this fifth edition presents a 12-point plan for ensuring success of campaigns of all sizes, covering vital areas including the role of public relations in organizations, the importance of context, research and analysis, setting objectives, strategy and tactics, timescales and resources, evaluation and review